Simulasi Monte Carlo untuk Memprediksi Jumlah Penerimaan Bantuan Sosial Pangan - Mulia, Jefri Rahmad; Afif, Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The implementation of food social assistance for people with disabilities and low-income families by the Social Office of Payakumbuh Barat Sub-District, Payakumbuh City, West Sumatra, is a local government initiative to address economic incapacity and limited access to basic needs. This program is designed to provide support to individuals with disabilities and families facing economic difficulties. Based on the research findings from 2021, there were 12 beneficiaries of food social assistance with an average percentage of 66.24%. Among them, 2 sub-districts had a presentation above 80%, while 10 sub-districts had a presentation below 80%. The accuracy of assistance distribution improved in 2022, with an average percentage of 98.38%. In this year, 6 sub-districts had a presentation above 80%, while 6 sub-districts had a presentation below 80%. The results of this research are expected to assist the Social Office of Payakumbuh Barat, Payakumbuh City, West Sumatra, in making informed decisions